Jobs Interventions for Refugees and Internally Displaced Persons - Schuettler, Kirsten (World Bank, Washington, DC, 2020)
This Jobs Solutions Note is intended to identify practical solutions for development practitioners and policymakers to design and implement policies and programs for the labor market integration of refugees and IDPs. The Note (a) identifies the specific obstacles that refugees and IDPs face when integrating the labor market, (b) highlights interventions designed to address those barriers, focusing on the World Bank, and (c) summarizes existing knowledge on what works. It builds on a comprehensive literature review on Jobs Interventions for Refugees and IDPs, and is part of a broader work on Supporting Jobs in Fragility, Conflict, and Violence Situations. The Note uses a broad definition of jobs as any income source, formal or informal, including employment, self-employment and entrepreneurship.